Nonequilibrium spherulitic magnetite in the Ryugu samples. (1st April 2023) - Dobrică, Elena; Ishii, Hope A.; Bradley, John P.; Ohtaki, Kenta; Brearley, Adrian J.; Noguchi, Takaaki; Matsumoto, Toru; Miyake, Akira; Igami, Yohei; Haruta, Mitsutaka; Saito, Hikaru; Hata, Satoshi; et al.
Abstract: We have investigated several particles collected during each of two touchdowns of the Hayabusa2 spacecraft at the surface of the C-type asteroid 162173 Ryugu using various electron microscope techniques. Our detailed transmission electron microscopy study shows the presence of magnetite with various morphologies coexisting in close proximity. This is characteristic of CI chondrite-like materials and consistent with the mineral assemblages and compositions in the Ryugu parent body. We describe the microstructural characteristics of magnetite with different morphologies, which could have resulted from the chemical conditions (growth vs. diffusion rate) during their formation. Furthermore, we describe the presence of magnetites with a spherulitic structure composed of individual radiating fibers that are characterized by pervasive, homogeneously distributed euhedral to subhedral pores that have not been described in previous chondrite studies. This particular spherulitic structure is consistent with crystallization under nonequilibrium conditions. Additionally, the presence of a high density of defects within the magnetite fibers, the high surface/volume ratio of this morphology, and the presence of amorphous materials in several pores and at the edges of the acicular fibers further support their formation under nonequilibrium conditions. We suggest that the growth processes that lead to this structure result from the solution reaching a supersaturated state, resulting in an adjustment to a lower free energy condition via nucleation and rapid growth.